Monitoring bone morphogenetic protein‐2 and ‐7, soluble receptor activator of nuclear factor‐κB ligand and osteoprotegerin levels in the peri‐implant sulcular fluid during the osseointegration of hydrophilic‐modified sandblasted acid‐etched and sandblasted acid‐etched surface dental implants. (4th April 2014) - Dolanmaz, D.; Saglam, M.; Inan, O.; Dundar, N.; Alniacık, G.; Gursoy Trak, B.; Kocak, E.; Hakki, S. S.
<x xml:space="preserve">Abstract</x> Background and Objective The implant surface plays a major role in the biological response to titanium dental implants. The aim of this study was to investigate levels of soluble receptor activator of nuclear factor‐κB ligand (sRANKL), osteoprotegerin (OPG), bone morphogenetic protein‐2 (BMP‐2) and ‐7 (BMP‐7) in the peri‐implant crevicular fluid (PICF) of different implants during the osseointegration period. Material and Methods Forty‐seven patients (22 females and 25 males, mean age 47.34 ± 10.11) were included in this study. Forty‐seven implants from two implant systems (group A1 (sandblasted acid‐etched [SLA]‐16), group A2 (hydrophilic‐modified SLA [SLActive]‐16), and group B (sandblasted acid‐etched [SLA]‐15) were placed using standard surgical protocols. PICF samples, plaque index, gingival index and probing depth measurements were obtained at 1 and 3 mo after surgery. PICF levels of sRANKL, OPG, BMP‐2/‐7 were analyzed by ELISA. Results No complications were observed during the healing period. No significant differences were observed in the PICF levels of sRANKL, OPG, BMP‐2 and BMP‐7 for all groups at any time point (p > 0.05). A significant decrease was observed in BMP‐2 levels in group A1 (p < 0.05). A significant increase in BMP‐7 levels was observed only for group A2 (p < 0.05). There was a strong negative correlation between OPG and gingival index and a negative correlation between BMP‐7 and plaque index (p < 0.05). Conclusion Considering the correlations between clinical and biochemical parameters, the levels of these cytokines in PICF during early healing of implants reflects the degree of peri‐implant inflammation, rather than differences in the implant surfaces.